Efficacy of multicomponent adsorption of fluoroquinolone based antibiotics onto the wasted municipal sewage sludge: Experiments and modeling - Rajib Kumar Das; Ujjaini Sarkar; Rohit Bhagat Kalwar (Cleaner Water)
Ciprofloxacin and ofloxacin are two important fluoroquinolone-based antibiotics that are heavily prescribed and consumed in Asian continent. Useful microbial consortium meant for biodegradation of sewage sludge get depleted in presence of these antibiotics. Additionally, the treated sewage wastewater, used in agricultural fields, municipal parks for gardening etc. still contain a large quantity of antibiotics. The specific objective of this piece of research work is to assess a specific scheme of in-situ batch equilibrium adsorption of these antibiotics using activated sludge at the specific sewage treatment works. Two models namely Modified competitive Langmuir-like model and LeVan-Vermeulen model are used for modelling the adsorption of ciprofloxacin and ofloxacin using activated sludge. Parameters from each of these models are evaluated using MATLAB and the fsolve MATLAB Library. The sludge and the post treated sludge after adsorption are characterized physically and chemically. A satisfactory fit for the Langmuir adsorption isotherm for both components in single component study implies the applicability of the multicomponent adsorption isotherm models in this study. Kinetics study, pore, and film diffusion models are also utilized. The goodness of the fits helps to conclude that film diffusion is the rate-controlling step for the adsorption of both ciprofloxacin and ofloxacin. Results demonstrate specific chemical interaction between ciprofloxacin with the negatively charged surface of the sewage sludge and surface complexation of ofloxacin with surface functional groups of the sewage sludge. Electrostatic interaction and surface coordination also show a vital role in the mechanism of adsorption of ciprofloxacin and ofloxacin onto the sludge.